EXUBERANT ULCERATED LESIONS OF SECONDARY SYPHILIS ON THE PALMS - AN UNUSUAL PRESENTATION - Dar, Nasser Rashid; Masood, Sadia; Raza, Naeem (Journal of Ayub Medical College Abbottabad, 2006)
Ulcerated lesions in secondary syphilis are rare. Exuberant tissue is seen in condylomas of syphilis, which occur in flexural and occluded areas of the body and not in open areas such as palms. We report a case of secondary syphilis that presented with ulcerated exuberant lesions on palms, which on initial examination gave an impression of lesions of Orf and Milker’s Nodule. Key words: Secondary Syphilis, Exuberant, Ulcerated lesions, Palms